Metabolism of 125I-labeled lipoproteins by the isolated rat lung (The Rockefeller University Press, 1976)
The capacity of the isolated perfused rat lung to metabolize the protein moieties of serum lipoproteins was assessed using homologous (rat) and heterologous (human) plasma lipoproteins. The protein and lipid moieties of the plasma lipoproteins were labeled in vivo with Na[125I]. In selected cases the lipoprotein peptides were labeled in vivo with 14C- or 3H-labeled amino acids. Uptake of lipoprotein label during perfusion was monitored by measure of losses in perfusate label and by rises in pulmonary tissue labeling as shown by radioassay and by light and electron microscope radioautography. Lipoprotein degradation was assessed by fractionation of perfusate and lung tissue radioactive material into trichloroacetic acid (TCA)-isoluble, TCA-soluble, and ether-ethanol-soluble fractions. When heparin was included in the perfusion medium, there was selective degradation of the protein portion of very low density lipoprotein (VLDL) in the perfusate and concomitant uptake of radioactive label by the lungs. Low density lipoprotein (LDL)) was neither taken up nor catabolized by the isolated rat lung in the absence or presence of heparin. By light and electron microscopy, the label was localized over the interalveolar septa, predominantly the capillary endothelium. Disappearance of TCA-insoluble radioactivity from the perfusate was associated with the generation of both TCA-soluble iodide and noniodide radioactivity. Greater than 50% of the radioactive label taken up by the lungs was found in the delipidated TCA-insoluble fraction. This study provides in vitro evidence for pulmonary catabolism of VLDL apolipoproteins and uptake of peptide catabolic products of VLDL by the lung.